2020
DOI: 10.1016/j.heliyon.2020.e03676
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic bianchi V cosmological model in Scale Covariant Theory of Gravitation with a time-variable deceleration parameter

Abstract: A spatially homogeneous and anisotropic Bianchi type V cosmological model of the universe for perfect fluid within the framework of Scale covariant theory of gravitation proposed by Canuto et al., is studied in view of a variable deceleration parameter which yields the average scale factor a(t) = sinh 1/n (βt), where n and β are positive constants. The solution represents a singular model of the universe. All physical and geometrical properties of the model are thoroughly studied. The time dependent decelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…From the observations of the researchers it is found that the deceleration parameter qshows a transition of the universe from initial decelerating phase to present accelerating phase [27][28][29][30][31][32][33][34]. For the acceleration of the universe it is required that the parameter q lies between −1 < q < 0 and for decelerating universe condition is q > 0.…”
Section: The Deceleration Parameter Qmentioning
confidence: 99%
See 1 more Smart Citation
“…From the observations of the researchers it is found that the deceleration parameter qshows a transition of the universe from initial decelerating phase to present accelerating phase [27][28][29][30][31][32][33][34]. For the acceleration of the universe it is required that the parameter q lies between −1 < q < 0 and for decelerating universe condition is q > 0.…”
Section: The Deceleration Parameter Qmentioning
confidence: 99%
“…From the observations of the researchers it is found that the deceleration parameter q shows a transition of the universe from initial decelerating phase to present accelerating phase [27][28][29][30][31][32][33][34].…”
Section: The Deceleration Parameter Qmentioning
confidence: 99%